Study on risk factors for mortality and morbidity in patients undergoing surgery for colorectal cancer - Kane, Varsha; Talpallikar, Mahesh C. (International Surgery Journal, 2019)
Background: The goal of surgery for colorectal cancer is cure, but post-operative mortality occurs. In evidence-based medicine, knowledge of the estimated risk associated with an operation might be an important factor to consider when a surgeon and patient consider surgery. This study aims to identify co-morbidity and causes of mortality in relation to direct technical complications of surgery. Methods: All consecutive patients who underwent surgery for colorectal cancer were included. Co-morbidity was determined. The postoperative course was studied and cause of death within 30 days was determined. The clinical and pathologic characteristics of patients were recorded by using detailed questionnaire. Results: 50 consecutive patients who underwent surgery for colon and rectal cancer were studied, out of which 3 died (6.45%). Most common cause for mortality was anastomotic leak and faecal peritonitis. 3 patients did not have any co-morbidities. In 14 patients (28%), duration of surgery was <3 hours, while in 36 patients (72%) operative time was >3 hours. No significant association was found between mode of surgery. Conclusions: The knowledge of independent perioperative risk factors responsible would help the surgeons to take the appropriate measures and shorten the stay and reduce post op mortality and morbidity. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>